2017
DOI: 10.1371/journal.pntd.0005645
|View full text |Cite
|
Sign up to set email alerts
|

Different features of Vδ2 T and NK cells in fatal and non-fatal human Ebola infections

Abstract: BackgroundHuman Ebola infection is characterized by a paralysis of the immune system. A signature of αβ T cells in fatal Ebola infection has been recently proposed, while the involvement of innate immune cells in the protection/pathogenesis of Ebola infection is unknown. Aim of this study was to analyze γδ T and NK cells in patients from the Ebola outbreak of 2014–2015 occurred in West Africa, and to assess their association with the clinical outcome.Methodology/Principal findingsNineteen Ebola-infected patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…Multiple lines of evidence since the late 1980s have shown that γδ T cells display strong activities against bacteria, including Mycobacterium tuberculosis ( 76 81 ); parasites, such as Plasmodium falciparum ( 82 86 ); and viruses ( 87 , 88 ), most notably CMV ( 89 91 ).…”
Section: Infected Cell Recognitionmentioning
confidence: 99%
“…Multiple lines of evidence since the late 1980s have shown that γδ T cells display strong activities against bacteria, including Mycobacterium tuberculosis ( 76 81 ); parasites, such as Plasmodium falciparum ( 82 86 ); and viruses ( 87 , 88 ), most notably CMV ( 89 91 ).…”
Section: Infected Cell Recognitionmentioning
confidence: 99%
“…The data suggest that a potent type 1 interferon response occurs in SHFV-inoculated rhesus monkeys, but it is unclear whether a similar response is present in SHFV-inoculated patas monkeys. NK cell responses are important for survival in human Ebola virus disease cases ( 28 , 29 ). Differences in the timing of NK cell responses are a key difference in non-lethal, mild disease and lethal, severe (Lassa virus) infections in macaques ( 30 ), suggesting the species-specific NK cell responses observed here warrant further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 is associated with T-cell exhaustion and is also found on activated T-cells ( 42 , 43 ). PD-1 + T-cells and CD8 + T-cells appear to play important roles in human cases of Ebola virus disease ( 28 , 29 , 4446 ). Consequently, it may be fruitful to determine if SHFV provides a means for studying the role of T-cell dysfunction in EVD.…”
Section: Discussionmentioning
confidence: 99%
“…Another key finding was the discovery natural killer (NK) cell transcriptional signatures present in mice that survived infection. NK cells have been of interest because of their association with survival of EBOV infections [ 56 , 57 ], thus supporting the transcriptional signature.…”
Section: Transcriptional Response To Ebola Virus Disease In Vivomentioning
confidence: 99%
“…Digital cell quantification (DCQ) analysis of the human data, using the transcriptional response to predict changes in cell populations, highlighted natural killer (NK) cell density increases correlating with survival [ 42 ], a finding that is supported by mouse DCQ analysis of EBOV infection [ 42 ]. NK cells have been shown to be increased in human survivors through FACS analysis [ 57 ]. Importantly, there was no increase in neutrophil markers in humans infected with EBOV, in sharp contrast with data obtained in NHPs.…”
Section: Transcriptional Response To Ebola Virus Disease In Humansmentioning
confidence: 99%